Optimizing the Performance of the Turjawali Sat Samapta Unit to Prevent Liquor Circulation in the Jurisdiction of the Pekalongan Police - Mukti, Muhammad Bima Dwi (Advances in Police Science Research Journal, 2024)
Alcohol is a dangerous drink and can cause crime. In accordance with regional regulations, alcohol is prohibited from being consumed in the Kabupaten Pekalongan. The participation of the National Police in overcoming the problem of circulation of alcohol in society is under the Samapta function. However, due to the large number of distribution of alcohol, the prevention efforts from Sat Samapta have not been carried out properly. This research uses a qualitative approach with data collection techniques in the form of observations, interviews, and campus studies. Based on the initial data obtained, the researcher conducted an analysis using SWOT theory and provided several alternatives to the analysis that had been carried out to reduce the amount of alcohol circulation, such as paying attention to the readiness and completeness of personnel equipment, providing training or personal additions, conducting internal and external supervision, providing punishment or rewards, optimizing budgets, maintaining patrol vehicles, forming Raimas platoons or installing Live Action cameras on vehicles. So that it can be concluded, the implementation of the performance of the Sat Samapta Patrol Unit of the Pekalongan Police is still not optimal and there needs to be an increase in preventing the circulation of alcohol in Kabupaten Pekalongan.